ENGINEERING DESIGN OF SWITCHING TRACK MECHANISM FOR METRO KAPSUL - Fahri Husen, Hilal
Switches are a crucial infrastructure component in the railway system. They are responsible for the process of changing the tracks for trains. This makes switches one of the main components supporting the operational performance of trains. In the metro kapsul, the track switching component differs from switches due to the difference in the steering process between the metro kapsul and conventional trains. In this final project, the design of a switching track mechanism for the metro kapsul is conducted. This research includes the selection of main components that support the performance of the track switching mechanism. One of the standards referred to is Ministerial Regulation No. 60 of 2012 regarding the technical requirements of railway tracks, and the selection of other track switching infrastructure components will refer to specific product catalogs. From this design process, a 23-degree turning angle on the guide track resulted in the smallest platform area for track switching, the suitable number of supports for the operational condition of the track switching infrastructure is 3 supports, the suitable linear bearing component for the operational condition is type SR 55 W, the suitable ball plunger component for the operational condition is GN 615-M24-KS, the suitable chain sprocket component for the operational condition of the track switching infrastructure is DID Chain 80 or equivalent to ANSI 80, the suitable motor for the operational condition is a geared motor type HA63 80B with foot mounting, and the suitable bearing component for the operational condition is UCP 210 accompanied by a pillow block.